3D-manufactured patient-specific models of congenital heart defects for communication in clinical practice: feasibility and acceptability. Issue 4 (30th April 2015) - Biglino, Giovanni; Capelli, Claudio; Wray, Jo; Schievano, Silvia; Leaver, Lindsay-Kay; Khambadkone, Sachin; Giardini, Alessandro; Derrick, Graham; Jones, Alexander; Taylor, Andrew M
Abstract : Objectives: To assess the communication potential of three-dimensional (3D) patient-specific models of congenital heart defects and their acceptability in clinical practice for cardiology consultations. Design: This was a questionnaire-based study in which participants were randomised into two groups: the 'model group' received a 3D model of the cardiac lesion(s) being discussed during their appointment, while the 'control group' had a routine visit. Setting: Outpatient clinic, cardiology follow-up visits. Participants: 103 parents of children with congenital heart disease were recruited (parental age: 43±8 years; patient age: 12±6 years). In order to have a 3D model made, patients needed to have a recent cardiac MRI examination; this was the crucial inclusion criterion. Interventions: Questionnaires were administered to the participants before and after the visits and an additional questionnaire was administered to the attending cardiologist. Main outcome measures: Rating (1–10) for the liking of the 3D model, its usefulness and the clarity of the explanation received were recorded, as well as rating (1–10) of the parental understanding and their engagement according to the cardiologist. Furthermore, parental knowledge was assessed by asking them to mark diagrams, tick keywords and provide free text answers. The duration of consultations was recorded and parent feedback collected. Results: Parents and cardiologists both found the models to be very useful and helpful in engaging the parents in discussing congenital heart defects. Parental knowledge was not associated with their level of education (p=0.2) and did not improve following their visit. Consultations involving 3D models lasted on average 5 min longer (p=0.02). Conclusions: Patient-specific models can enhance engagement with parents and improve communication between cardiologists and parents, potentially impacting on parent and patient psychological adjustment following treatment. However, in the short-term, parental understanding of their child's condition did not improve.